Inclusion And Learning: Factors Affecting Students With Intellectual Disabilities - Saratikyan, Lilit
The purpose of the article is to identify the factors affecting the educational activity of students with intellectual disabilities, under the conditions of the principle of universal formation of learning, which will provide an opportunity to develop the practical orientation of the pedagogical and psychological support services provided to them. Research conducted among 119 teachers and 32, students with intellectual disabilities (8-10-year-old) from 25 general basic schools in Yerevan, Lori, Ararat, Tavush, Kotayk regions of the Republic of Armenia has allowed us to identify the factors affecting the learning process of students with intellectual disabilities, which cause many psycho-pedagogical problems in school. The research was based on the issues identified during the additional special pedagogical support provided to these students, the complaints registered by the parents and the difficulties of the educators working with them, which are mainly related to the organization of joint learning and insufficient pedagogical conditions.
Keywords: Pedagogy; Psychology